How Information-Seeking Behavior, Essential Technologies, and Resilience Enhance the Academic Performance of Students - Miraj, Muhammad; Chuntian, Lu; Mohd Said, Ridzwana; Osei-Bonsu, Robert; Rehman, Ramiz ur (Frontiers in Psychology, 2021)
This study explores how the scholarly accomplishments of students might increment due to specific fundamental causes. The academic performance of the student was prioritized as a dependent variable, and the independent indicators chosen were “information seeking, IT ability, reading/writing capacity, and resilience.” At the same time, age, gender, marital status, and family income were included in the control variables. The research subject samples were limited to (N = 288) postgraduate students from three mega universities in Islamabad, Pakistan. Forward regression analysis was performed in this research to decide the impact of the indicators. The results indicate that information seeking affects academic performance positively and significantly. Essentially, the study revealed that information technology (IT) skills make a fundamentally positive and significant impact on academic performance. Reading and writing influenced academic performance considerably. In addition, resilience affected academic performance emphatically and essentially. Further, this research also noted the relationships between information-seeking behaviors, IT ability, reading/writing capacities, and resilience capabilities and the academic performance of students. These variables have a positive impact on the academic performance of students.